Multi-objective optimal configurations of a membrane reactor for steam methane reforming - Penglei Li; Lingen Chen; Shaojun Xia; Rui Kong; Yanlin Ge (Energy Reports, 2022)
The combination of traditional reactor and permeable membrane is beneficial to increase the production rate of the target product. How to design a high efficiency and energy saving membrane reactor is one of the key problems to be solved urgently. This paper utilizes finite-time thermodynamics and nonlinear programming to solve the optimal configurations of the membrane reactor of steam methane reforming (MR-SMR) for two optimization objectives, that is, heat exchange rate minimization and power consumption minimization. The exterior wall temperature and fixed hydrogen production rate are regarded as the control variable and constraint, respectively. The results indicate that the hydrogen production rate and heat exchange rate in MR-SMR are increased by 108.58% and 58.42%, respectively, while the power consumption is reduced by 33.44% compared with those in the traditional reactor under the same condition. Compared with the results in reference reactor (MR-SMR obtained with initial values), the heat exchange rate is reduced by 1.40% by optimizing the exterior wall temperature, and the power consumption is reduced by 5.10% by optimizing the exterior wall temperature and molar flow rate of sweep gas. The optimal distributions of exterior wall temperatures in the optimal reactors of minimum heat exchange rate and power consumption have a theoretical guiding significance for the thermal design of the membrane reactors.